The Catalytic Investigation of Supported Imidazolium-chloroaluminate (AlCl3-lLs) in Friedel-Craft Acylation of Anisole - Thiti Junpirom (Science Faculty of Chiang Mai University, 2019)
Two AlCl3 supported imidazolium salts (1, 2) were prepared and utilized as the catalysts for the acylation of anisole. The standard conditions for the reaction were optimized. The acylation of anisole using those AlCl3 supported imidazolium provided the desired product in high percentage yield in a short period of time. The results revealed that AlCl3 supported imidazolium salts are suitable for this reaction when the molar ratio of AlCl3: imidazolium is 2:1 and the reaction smoothly proceeded even at the low temperature such as 0 oC. Moreover, the AlCl3-supported catalyst 1 demonstrated the promising reusability after being catalytically used for 3 times without losing properties.